2011
DOI: 10.1007/s10584-011-0244-0
|View full text |Cite
|
Sign up to set email alerts
|

Air quality planning in California’s changing climate

Abstract: California is home to some of the worst air quality in the nation and ninety percent of the state's population lives in areas that are out of attainment with at least one of the National Ambient Air Quality Standards. Increasing temperatures associated with climate change will make meeting air quality standards more difficult. Under a changing climate, additional emission reductions will be needed to achieve clean air standards. These additional emission reductions and associated costs are called the "climate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…24 The San Joaquin Valley air basin, one of the most populous in the state, is projected to experience large population growth and has a high probability of exceeding air quality standards for ground-level ozone. 27 Projected increases in emissions of air pollutants coupled with population projections for this air basin under both B1 and A2 climate scenarios for late-century suggest that an additional 1.5−5.5 million people may be impacted by degraded air quality (Figure 3). This potential presents a significant challenge for climate change adaptation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…24 The San Joaquin Valley air basin, one of the most populous in the state, is projected to experience large population growth and has a high probability of exceeding air quality standards for ground-level ozone. 27 Projected increases in emissions of air pollutants coupled with population projections for this air basin under both B1 and A2 climate scenarios for late-century suggest that an additional 1.5−5.5 million people may be impacted by degraded air quality (Figure 3). This potential presents a significant challenge for climate change adaptation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Extended fire seasons will affect both scenery and air quality, with detrimental effects to human health. Analyses of the effects of climate change on air pollution in general have shown that climate change will increase the severity and duration of air pollution episodes (Bedsworth 2011). Climate change may affect distribution patterns and mixtures of air pollutants through altered wind patterns and amount and intensity of precipitation.…”
Section: Effects Of Climate Changementioning
confidence: 99%
“…The disastrous wildfire season exposed more than half of California's population to the highest number of severe air pollution days in the state's recorded history (Safford et al., 2022 ). The California Fourth Climate Assessment report projects that the state's wildfire burn area may increase 77% by the end of the century (Bedsworth et al., 2018 ). The likelihood of numerous climate‐related hazardous events, such as extreme heat, occurring simultaneously has increased in the state (Rosenthal et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%